Etika Kerja Islam: Kunci dalam Meningkatkan Motivasi Pegawai di Dinas Lingkungan Hidup Kabupaten Magelang - Aqni, Bima Vitrana; Purwanto; M Pudail (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this research is to analyse the relationship between Islamic work ethics and employee work motivation at the DLH of Magelang Regency. In order to achieve the research objectives, this study uses a qualitative approach. Research data were collected using in-depth interviews. Interviews were conducted with one leader and five employees of the DLH Kabupaten Magelang. The research data were subsequently analysed using an interactive model, which has been validated using source triangulation. The results of this study indicate that Islamic work ethics can enhance employee work motivation. For example, in the principle of Tawhid, employees who believe that work is part of their religion have higher intrinsic motivation. In the principle of Balance and Justice, employees who receive trust and fairness from their superiors have higher extrinsic motivation. In the principle of Free Will, employees who have the freedom to express their opinions and tolerate discussions have higher intrinsic motivation. In the principle of Responsibility, employees who feel a sense of responsibility in carrying out their tasks and work have higher intrinsic motivation. In the principle of Virtue or Truth, employees who believe that instilling virtues such as honesty, discipline, and responsibility is part of religious commandments have higher intrinsic motivation.